2022
DOI: 10.3389/fendo.2022.863541
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles and Therapeutic Implications of Epigenetic Modifications in Ovarian Cancer

Abstract: Ovarian cancer (OC) is one of the most lethal gynecologic malignancies globally. In spite of positive responses to initial therapy, the overall survival rates of OC patients remain poor due to the development of drug resistance and consequent cancer recurrence. Indeed, intensive studies have been conducted to unravel the molecular mechanisms underlying OC therapeutic resistance. Besides, emerging evidence suggests a crucial role for epigenetic modifications, namely, DNA methylation, histone modifications, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 207 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…showed that the application of epigenetic approaches for the diagnosis, clinical treatment, and prognosis of OC is a promising area for future clinical research 307–310 . New evidence suggests that epigenetic changes have important implications in OC drug resistance 311,312 . Abbosh et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%
See 2 more Smart Citations
“…showed that the application of epigenetic approaches for the diagnosis, clinical treatment, and prognosis of OC is a promising area for future clinical research 307–310 . New evidence suggests that epigenetic changes have important implications in OC drug resistance 311,312 . Abbosh et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%
“…[307][308][309][310] New evidence suggests that epigenetic changes have important implications in OC drug resistance. 311,312 Abbosh et al found that inhibiting H3K27 methylation re-sensitizes drug-resistant OC cells to cisplatin. 313 Moreover, loss of H3K27me3 can increase the expression of tumor suppressor genes, thereby leading to the occurrence of tumors.…”
Section: Ovarian Cancer (Oc)mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is not the only epigenetic mechanism involved in carcinogenesis. Histone modifications and chromatin packaging play an important role in genome regulation in cancers [ 72 ]. In ovarian cancer specifically, histone marks such as the repressive H3K27me3 mark and active H3K4me3 mark are considered markers of bivalent genes, poised to be silenced during drug resistance in ovarian cancers, particularly regulated by the EZH2 protein complex [ 73 ].…”
Section: Epigenetic Changes Induced By Cocpmentioning
confidence: 99%
“…Genetic mutations have been reported to associate with ovarian cancer progression, such as BRCA1 (breast cancer 1) mutation and BRCA2 (breast cancer 2) mutation ( Sanchez-Lorenzo et al, 2022 ). Moreover, epigenetic regulation has been revealed to participate in the development of ovarian cancer ( Wang et al, 2022a ; Zhao et al, 2022 ). It is known that epigenetics refers to heritable changes and do not change DNA sequence.…”
Section: Introductionmentioning
confidence: 99%